Global oncology : Harvard Global Health Catalyst summit lecture notes - Ngwa, Wilfred; Nguyen, Paul L. (IOP (Series). Release 3., 2017)
The material presented in this book is at the cutting-edge of global oncology and provides highly illuminating examples, addresses frequently asked questions, and provides information and a reference for future work in global oncology care, research, education, and outreach.